Using high level validation to increase lake ecosystem model reliability. (April 2023) - Regev, Shajar; Carmel, Yohay; Gal, Gideon
Abstract: Lake ecosystem models are essential for capturing ecosystem response to climate change and for studying eutrophication. Model ability to capture ecosystem dynamics is limited for various reasons. Aiming to increase confidence in simulations of future scenarios, the current study adapts a recently established four level validation framework, named CSPS (Conceptual, State, Process and System validation). Lake ecosystem model WET was calibrated for lake Kinneret and validated using the CSPS framework, inspecting 18 state variables, 11 processes and 15 emergent properties. Validation showed that most processes and emergent properties were correctly simulated with some weaknesses revealed such as light attenuation and particle dynamics. Modifying the model to overcome those weaknesses will result in increased model reliability. This conclusion would have been impossible without the process validation. We conclude that higher validation levels are necessary to receive reliable results when running process-based lake models on future scenarios. Highlights: High level validation (CSPS) was applied for WET Lake ecosystem model. Most processes and emergent properties were correctly simulated. Validation revealed model weaknesses such as particle dynamics. Higher validation levels are necessary to increase ecosystem model reliability.